EFFECT OF ZEOLITE 4A ON WATER CONCENTRATION IN THE SYSTEM OF THE ESTERIFICATION REACTION OF ACETIC ACID WITH 1-BUTANOL - Ratna Dewi Kusumaningtyas (Indonesian Journal of Chemistry, 2006)
The usual problem encountered on a reversible reaction is that the reaction cannot achieve a complete conversion of reactants since it is limited by the thermodynamic equilibrium. Due to this low conversion, it will face challenges with product purification and recycling of the reactants, which then cause an increase in the operation cost. To obtain higher conversion, it is necessary to shift the equilibrium towards the products by continuously removing the water formed. One popular example of reversible reaction is esterification process. In this research, water removal was conducted through an adsorption process using zeolite 4A. Effect of zeolite 4A on water concentration in the liquid phase esterification of acetic acid and 1-butanol catalyzed by sulfuric acid was investigated. It was performed in an isothermal batch reactor. The molar ratio of 1-butanol - acetic acid was 1.4 times theoretically, the catalyst concentration was 1 % wt and the mixing intensity was 1000 rpm. The influence of the temperature was studied at 40 to 80 °C and the zeolite 4A loading was varied at 1.6 to 5.52 % w/ v. The reaction was compared to the conventional esterification reaction carried out under identical conditions but without addition of zeolite 4A. Concentration of each component in the system was analyzed using on-line Gas Chromatography. Effect of removing the water produced during the reaction by using zeolite 4A was demonstrated. It was revealed that the amount of water removed was proportional to the amount of the zeolite 4A to be employed. On the other hand, the increase of the temperature led to the lower amount of water to be adsorbed. Among all the experiments, the best result was achieved on the addition of 5.52 % b/v zeolite 4A at 40 °C, where water concentration was 3.1356 g mole/L and the conversion was 76.11 % at the equilibrium condition. As comparison, water concentration on the conventional reaction performed at 40 °C was 6.9161 g mole/L and the conversion was 62.5 % at the equilibrium condition. The equation illustrating the effect of zeolite 4A loading on the conversion obtained at the equilibrium condition was: XAe = 0.6248 + 0.0868 C4A0.2848, where XAe was equilibrium conversion of Acetic Acid and C4A was Zeolite 4A loading (g/100 mL liquid).